Model Deteksi Kecurangan Berbasis Fraud Triangle - Sukirman, Sukirman; Sari, Maylia Pramono (Department of Accounting, Faculty of Economics & Business,Diponegoro University, Indonesia, 2013)
The case of issuers violation in stock market is one of the most frequent case that should besolved by the stock market’s Regulator Board. In Indonesia, the authority to do the surveillance instock exchanges is handled by the Capital Market Supervisory Agency and Financial Institution(or called ‘Bapepam-LK’ in Indonesian). There is a gap between society’s expectation towardBapepam-LK as the regulator and its performance in solving several companies violation caseswhich demands some alternative solutions. Based on the above description, this study willempirically investigate the development of fraud detection model using fraud triangle based onthe cases of violation committed by public companies in Indonesia. In detail, the problems inthis research are: (1) Is there any difference related to the triggering factors of Fraud Trianglebetween the company that commits fraud and the company that does not; (2) Is there any differencein terms of pressure between the company that commits fraud and the company that does not;(3) Is there any difference in terms of opportunity between the company that commits fraud andthe company that does not; (4) Is there any difference in terms of rationalization between thecompany that commits fraud and the company that does not. This research was carried out to thepublic companies who are registered in Indonesia Stock Exchanges (BEJ). Generally, there aretwo sample group in this research. The first sample group consiststed of the companies who hadcommitted fraud and the second group as comparison consisted of the non-fraud companies. Inthis research there are 98 companies as the research samples which consisted of 23 companieswho had committed fraud and 75 companies who did not commit fraud. The analysis tool usedfor this research was logistic regression because the measurements of dependent variable usedthe categorical that is dummy variable, code (0) was used for the non-fraud companies and code(1) was used to indicate the companies who committed fraud. The research result shows that fromfour hypothesis proposed in this research, only one variable which fits in to the model (variablein equation) because posesses the significance score above 0.05. The interpretation is that thehigher the audit report (rationalization), will make the company’s probability to commit fraud isalso higher. From the above explanation, it can be concluded that the fourth hypothesis (H4) isaccepted because the audit report (rationalization) is proven to have the ability in forming themodel to predict fraud in a company.